The Impact Human Development Index and Industrial Labor on Economic Growth in North Sumatra Province - Efendi, Bakhtiar; Nasution , Diwayana Putri; Rusiadi, Rusiadi; Pratiwi, Devani (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Economic growth in North Sumatra remains a critical focus due to regional disparities in human development and industrial productivity. This study aims to analyze the impact of the Human Development Index and Industrial Labor on economic growth across 33 regencies/cities from 2010 to 2022. A quantitative approach using multiple linear regression with a fixed-effects model was employed, utilizing panel data from official statistics on the Human Development Index, Industrial Labor, and Gross Regional Domestic Product. The findings reveal that the Human Development Index has a significant but negative effect on economic growth, suggesting inefficiencies in translating human capital improvements into economic outcomes. Industrial Labor shows a positive but insignificant effect, likely due to low workforce skills. However, the combined effect of the Human Development Index and Industrial Labor significantly influences economic growth, indicating a synergistic relationship. The study concludes that targeted policies to enhance education, healthcare, and vocational training are essential to maximize the economic contributions of human development and industrial labor, particularly in rural areas, to foster sustainable economic growth in North Sumatra.